Penguatan Strategi Pemasaran UMKM di masa Pandemi Covid-19: Studi Kasus Pelaku Usaha Tenun di Kabupaten Kulon Progo - Kristiana Sri Utami (Universitas Proklamasi 45, 2022)
The national economy experienced a slump at the beginning of 2020. The Covid-19 pandemic has reduced economic activity which has an impact on a decline in economic growth. SMEs (Small and Medium Enterprises) as the backbone of the national economy during the 2018 monetary crisis experienced a sharp decline in growth due to the Covid-19 pandemic. The revival of SMEs has a big role in the revival of the national economy. This study aims to analyze the right marketing strategy for woven fabric SMEs in Kulon Progo Regency during the Covid-19 pandemic. This study uses qualitative descriptive analysis of 32 business actors who were selected as informants with certain criteria. The type of data collected is primary data. The data analysis method used in this study is SWOT which consists of Strengths, Weaknesses, Opportunities, and Threats. The results of the analysis show that the most appropriate marketing strategy for woven fabric SMEs in Kulon Progo Regency during the Covid-19 pandemic is a turn-around strategy through increasing human resource capabilities in the use of information technology media; increasing digital marketing through the use of social media such as WhatsApp, Facebook, Instagram, Twitter and website in promoting products; utilizing and improving communication links to form partnerships between business actors in various fields; and improving management for business units.